The Prevalence of Formal Risk Adjustment in Health Plan Purchasing - Patricia Seliger Keenan; Melinda J. Beeuwkes Buntin; Thomas G. McGuire; Joseph P. Newhouse (SAGE Publishing, 2001)
This paper describes the prevalence of formal risk adjustment of payments made to health plans by Medicare, Medicaid, state governments, and private payers. In this paper, "formal risk adjustment" is defined as the adjustment of premiums paid to health plans based on individual-level diagnostic or demographic information. We find that formal risk adjustment is used for about one-fifth of all enrollees in capitated health plans. While the Medicare and Medicaid programs rely on formal risk adjustment for virtually all their health plan enrollees, the practice is used for only about 1% of privately insured health plan enrollees. Our findings raise the question of why regulators have adopted formal risk adjustment, but private purchasers for the most part have not.